Energy efficiency in the industry: A step to increase productivity - Elizabeth Cruz (Instituto de Ingenieros de Minas del Peru, 2009)
The paper point out innovative energy management techniques that lead to energy recovery and uses it back in the process as heat, mechanical work or power with a consequent impact on operating cost and operating cost and operation cost and a reduction in the overall enviroment impact.